Preparation, characterization and degradation of linear low density polyethylene/rambutan peel flour biocomposites
Nowadays, developments of plastics from biodegradable polymers and natural filler have attracted great interests in science and research. Biodegradable polymer could allow complete degradation in soil and does not emit any toxic or noxious components. Therefore, in this research, an attempt was made by incorporating rambutan peel flour (RPF) into LLDPE matrix. This study investigated the influence of adipic acid as compatibilizer on the properties of the composites prepared from LLDPE with different RPF loading varied from 5 to 25 wt%. Cobalt stearate (CS) as a pro-oxidant (0.2 wt%) has been added into LLDPE/RPF-AA composites. Natural weathering and soil burial test were performed for 9 months’ period to determine the potential of this polymer to degrade in different surroundings. As a result, LLDPE/RPF-AA composites showed higher tensile strength and elongation at break (Eb) compared to LLDPE/RPF composites after weathering and composting exposure. However, after the addition of CS, the tensile strength and Eb of LLDPE/RPF-AA composites decreased. Scanning electron microscopy (SEM) micrographs showed the formation of cracks, pores and fungus colonization on the LLDPE/RPF composites and LLDPE/RPF-AA composites surface. For differential scanning calorimetry (DSC) analysis, LLDPE/RPF-AA composites presented higher crystallinity compared to the LLDPE/RPF composites. The thermal stability for the composites decreased from 429 °C (LLDPE) to 251 °c for 25 wt% of RPF and 262 °c for 25 wt% of RPF-AA.